Administration of RAS Inhibitor before the Onset of Diabetic Nephropathy Counteracts the Adverse Effect of Chronic Hyperglycemia and Reduces the Augmentation of Urinary Albumin Excretion: A Retrospective Clinical Study - Hidenori Hirukawa; Shinji Kamei; Tomohiko Kimura; Atsushi Obata; Kenji Kohara; Fuminori Tatsumi; Masashi Shimoda; Shuhei Nakanishi; Tomoatsu Mune; Kohei Kaku; Hideaki Kaneto (Journal of Diabetes Research)
It is very important to explore how we can reduce urinary albumin excretion which is an independent risk factor for ischemic heart disease. In this study, we retrospectively evaluated the effects of RAS inhibitor therapy on diabetic nephropathy in Japanese subjects whose urinary albumin levels were within normal range. We enrolled 100 subjects with type 2 diabetes who did not take any renin-angiotensin system (RAS) inhibitor. We defined the subjects taking RAS inhibitor for more than 3 years as RAS inhibitor group. RAS inhibitor exerted protective effect on the progression of urinary albumin excretion in subjects with type 2 diabetes without diabetic nephropathy. In addition, RAS inhibitor exerted more protective effects on renal function especially in subjects with poor glycemic control. In conclusion, RAS inhibitor could protect renal function against the deleterious effect of chronic hyperglycemia in Japanese subjects with type 2 diabetes even before the onset of diabetic nephropathy.